Evaluation of the Physico-Chemical Characteristics and Sensory Qualities of Mackerel and Horse Mackerel Smoked with Fruit Peels and Rice Husk Residues in Benin - SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; vinankpon, Sabine; KIKI, Pascal; AGOSSA, Raoul; KONSAKA, BERNADETTE M.; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2021)
moked fish quality depends on the fuel used for smoking. This study aimed to improve smoked fish quality using fruit peels, rice husks, and palm kernel charcoal (PCH) as fuels. Thirty fish (15 Atlantic mackerel and 15 horse mackerel) were smoked traditionally, while 75 horse mackerel and 75 Atlantic mackerel were smoked with experimental fuels. Physico-chemical characteristics and sensory quality of the smoked fish were assessed. The highest weight loss after smoking was found for the fish smoked with pineapple skin (32.79%), peanut shells (30.06%), and orange peel (29.84). The skin color of the fish smoked with rice husks was less white, redder, and more yellowish than the other fish. Those smoked traditionally had darker skin. The sensory quality of the fish smoked with rice husks, pineapple skin, and peanut shells was more acceptable. In summary, these fuels can be used to improve the appearance and quality of smoked products.
Keywords: Fih; smoking quality; fruit peelings; crop residues